Circulating microRNAs associated with prolonged overall survival in lung cancer patients treated with nivolumab. (2nd September 2018) - Halvorsen, Ann Rita; Sandhu, Vandana; Sprauten, Mette; Flote, Vidar G.; Kure, Elin H.; Brustugun, Odd Terje; Helland, Åslaug
Abstract: Background: The introduction of immune check-point inhibition in non-small cell lung cancer (NSCLC) therapy represents improved prospects for the patients. The response rates to check-point inhibitors are approximately 20% in unselected NSCLC patients. Increasing levels of tumor PD-L1 expression are associated with higher response rates. However, patients with low PD-L1 levels may also have durable responses, and improved strategies for patient stratification are needed. Material and methods: In this study, we investigated circulating microRNAs aiming to identify circulating predictive biomarkers associated with increased overall survival after immune check-point treatment. Using next generation sequencing, we performed microRNA profiling in serum from NSCLC patients ( n  = 20) treated with nivolumab. Serum samples from 31 patients were used for validation using qPCR assays. Serum samples were collected prior to immune therapy initiation. Results: Based on multivariate regression analysis, we identified a signature of seven microRNAs (miR-215-5p, miR-411-3p, miR-493-5p, miR-494-3p, miR-495-3p, miR-548j-5p and miR-93-3p) significantly associated with overall survival (OS) > 6 months in discovery cohort ( p  = .0003). We further validated this in another similar set of samples ( n  = 31) and the model was significantly associated with overall survival (OS) > 6 months ( p  = .001) with sensitivity and specificity of 71% and 90%, respectively. Conclusions: In this study of circulating microRNAs, we have identified a 7-miR signature associated with survival in nivolumab-treated NSCLC patients. This signature may lead to better treatment options for patients with NSCLC, but a validation in an independent cohort is needed to confirm the predicted potential.